2017
DOI: 10.1302/1863-2548.11.160212
|View full text |Cite
|
Sign up to set email alerts
|

Femoral neck fractures in osteogenesis imperfecta treated with bisphosphonates

Abstract: PurposeOsteogenesis imperfecta (OI) is a condition characterised by bone fragility and multiple fractures, which cause considerable morbidity in the affected patients. Most cases are associated with mutations in one of the type I collagen genes. Recently, bisphosponates have been used widely to reduce pain and the incidence of fragility fractures in OI in children, even though there have been concerns raised regarding the long-term complications of it due to their effect on the bone. The fragility fractures in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…Similar to most studies, the most common cause of FNFs in our studied population was secondary to a fall injury, which was documented in 37 patients (53.6%), followed by RTA in 16 patients (23.2%, Table 2 ). This finding is likely because most of our patients who had a fall injury were middle-aged males (mean age of 42.8 ± 19.1 years) with some co-morbid conditions such as DM and HTN, and RTA was found among younger adult males (mean age of 31.8 ± 5.2 years) without any co-morbid conditions [ [1] , [2] , [3] , [4] ]. Understandably, older men who have co-morbid conditions have a higher risk of fall injuries compared to females in this study since most of the comorbid conditions, such as DM and HTN, were seen among our male patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to most studies, the most common cause of FNFs in our studied population was secondary to a fall injury, which was documented in 37 patients (53.6%), followed by RTA in 16 patients (23.2%, Table 2 ). This finding is likely because most of our patients who had a fall injury were middle-aged males (mean age of 42.8 ± 19.1 years) with some co-morbid conditions such as DM and HTN, and RTA was found among younger adult males (mean age of 31.8 ± 5.2 years) without any co-morbid conditions [ [1] , [2] , [3] , [4] ]. Understandably, older men who have co-morbid conditions have a higher risk of fall injuries compared to females in this study since most of the comorbid conditions, such as DM and HTN, were seen among our male patients.…”
Section: Discussionmentioning
confidence: 99%
“…Femoral neck fractures (FNFs) are fractures of the flattened pyramidal bone connecting the femoral head and the femoral shaft. It is not common in healthy individuals but common among athletes, military recruits, and young adults because of high energy activities such as sports and road traffic accidents, in adults because of falls, in women because of estrogen imbalances, and in patients because of bone mineralization and deficiencies [ [1] , [2] , [3] , [4] ]. In the USA in 2013, there were a reported 146 cases per 100,000 people [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The femoral neck fracture was managed with operative stabilization using cannulated screws around the preexisting IM rod. The difficulty in treating femoral neck fractures around preexisting IM rod in patients with OI has been reported previously in few reports [4,5,18]. The ipsilateral incomplete AFF was initially managed conservatively due to fracture location around the IM implant.…”
Section: Discussionmentioning
confidence: 96%
“…Adolescents with OI are commonly treated with bisphosphonates to increase bone mineral density, reduce the incidence of fracture, and reduce bone pain [1][2][3]. Treatment of femoral neck fractures in patients with OI treated with cannulated screw fixation around a preexisting intramedullary (IM) rod poses a unique challenge in management, with few reports publishing successful outcomes [4][5][6] Nonetheless, there are increasing concerns regarding longterm effects of bisphosphonate treatment in adults for osteoporosis, and cases of atypical subtrochanteric femur fractures with long-term bisphosphonate use have been well described in the literature [7][8][9]. Nicolaou et al, described the pattern of complete subtrochanteric femur fractures that occur with bisphosphonate use in patients with OI, including 38% occurring in rodded femora [10].…”
Section: Introductionmentioning
confidence: 99%
“…Chow's own series of 5 patients added to a total of 20 reported femoral neck fractures in OI. Papanna et al 8) reported on 7 pediatric patients (11 hips) with OI treated with a cannulated headless screw. All of them had been on bisphosphonates.…”
Section: Discussionmentioning
confidence: 99%